Sustainable Development and Yield, Morphological, Biochemical and Ecotoxicological Characterization of Banana Peel Biofertilizer - Costa, Juliana Dantas da; Silva, Melissa Castro da; Aguiar, Ana Beatrice Melo; Silveira, Matheus Sousa; Costa, Tamiris Bezerra; Castro-Silva, Igor Iuco (Fronteira: Journal of Social, Technological and Environmental Science, 2025)
Organic fertilizers derived from solid food waste, such as banana peels, represent a promising circular model for mitigating waste and enhancing biotechnological innovation. This study aimed at the sustainable development of a biofertilizer from discarded Musa sapientum peels. Fresh samples were obtained through selective collection in a university restaurant in the interior of Ceará and carried out quantitative indicators. Pilot study with four collections tested different time-temperature processing for dehydration and flour prototyping. Based on the best morphological aspects of pilots 3 and 4, the operational protocol was chosen for the second phase, with eleven collections subjected to a continuous cycle of automated dehydration at 70oC for 12h, grinding and sieving. The yields of each cycle were analyzed, considering the weight of wet and dry matter. Biochemical analysis detected the presence of the macronutrient nitrogen, phosphorus and potassium and pH in aqueous solution in quintuplicates. Ecotoxicological analysis was conducted in an Artemia salina model for 24h of direct contact with three batches of fertilizer in different concentrations and in quadruplicate. Banana peel was an economical option, and the chosen protocol provided a homogeneous product with medium grain size. Despite the substantial reduction in sample volume, there was a predictable yield of an average of 10.3%, suggesting potential for scalability. The concentration of macronutrients remained within the expected range for a fertilizer for acidic soils, with low nitrogen and high phosphorus and potassium content, which explains the alkalizing effect on pH. There was no toxicity at the low concentrations tested up to 10,000µg/mL, maintaining a lethal concentration below 50%. Banana peel flour showed favorable structural properties for use as biofertilizer. Future studies will be able to elucidate its effectiveness in green areas on the campus and the impact on environmental compliance of the endogenous demand for waste at the university.